2017
DOI: 10.1002/pam.22039
|View full text |Cite
|
Sign up to set email alerts
|

Can Financial Aid Help to Address the Growing Need for STEM Education? The Effects of Need‐Based Grants on the Completion of Science, Technology, Engineering, and Math Courses and Degrees

Abstract: Although workers in science, technology, engineering, and math (STEM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Eligibility increases STEM degree receipt within four years of entry by 33 percent and by 16 percent within six years of entry. These increases are larger than most of the estimated impacts of federal SMART (Science and Mathematics Access to Retain Talent) grants, which explicitly subsidized STEM degree completion (e.g., Denning and Turley 2017; Evans 2017) and similar to the findings of Castleman et al (2017), who study the effect of a state need-based grant that did not explicitly incentivize STEM. We find a marginally significant (p < 0.1) increase in the share of students who declare a STEM major during their time in college (Online Appendix Table C.7), which could arise if treatment effects on attainment are larger for STEM majors or if a maximum Pell Grant affects sorting into and/or out of STEM majors.…”
Section: Channels For Earnings Gainsmentioning
confidence: 79%
See 1 more Smart Citation
“…Eligibility increases STEM degree receipt within four years of entry by 33 percent and by 16 percent within six years of entry. These increases are larger than most of the estimated impacts of federal SMART (Science and Mathematics Access to Retain Talent) grants, which explicitly subsidized STEM degree completion (e.g., Denning and Turley 2017; Evans 2017) and similar to the findings of Castleman et al (2017), who study the effect of a state need-based grant that did not explicitly incentivize STEM. We find a marginally significant (p < 0.1) increase in the share of students who declare a STEM major during their time in college (Online Appendix Table C.7), which could arise if treatment effects on attainment are larger for STEM majors or if a maximum Pell Grant affects sorting into and/or out of STEM majors.…”
Section: Channels For Earnings Gainsmentioning
confidence: 79%
“…Prospective students' college enrollment decisions generally respond to changes in prices driven by variation in tuition and grant aid provided by simple, easily accessed programs (Deming and Dynarski 2010). A handful of studies find evidence that eligibility for state grant aid shifts students into college, across different types of institutions, and into degree receipt (e.g., Scott-Clayton 2011; Castleman and Long 2016;Bettinger et al 2016;Scott-Clayton and Zafar 2016). As our model highlights, a policy that causes students to shift across sectors may have very different welfare implications than a policy that increases degree receipt.…”
Section: Introductionmentioning
confidence: 99%
“…See Deming and Dynarski () for a summary of these studies. Several studies have found financial aid and tuition to affect enrollment (Cornwell, Mustard, & Sridhar, ; Denning, ; Dynarksi, ), graduation (Bettinger et al., ; Castleman & Long, ; Denning, forthcoming; Denning, Marx, & Turner, forthcoming), and college major (Castleman, Long, & Mabel, ; Denning & Turley, ).…”
mentioning
confidence: 99%
“…Next, in Tables A6 and A7 (available in the online version of the journal), we examined sensitivity to the choice of bandwidths. Similar to other scholars (e.g., Castleman et al, 2017), the main analysis is based on a midpoint from a range of bandwidths specified after estimating developmental math progression and STEM participation outcomes. We examined the sensitivity of the results by calculating the optimal bandwidth (Calonico et al, 2017).…”
Section: Sensitivity Analysesmentioning
confidence: 99%